2008
DOI: 10.1111/j.1539-6924.2008.01055.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Modeling of Emergency Events: Assessing the Impact of Hypothetical Releases of Anthrax

Abstract: A modular system for source-to-dose-to-effect modeling analysis has been developed based on the modeling environment for total risk studies (MENTOR),(1) and applied to study the impacts of hypothetical atmospheric releases of anthrax spores. The system, MENTOR-2E (MENTOR for Emergency Events), provides mechanistically consistent analysis of inhalation exposures for various release scenarios, while allowing consideration of specific susceptible subpopulations (such as the elderly) at the resolution of individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 50 publications
2
23
0
Order By: Relevance
“…For outdoor releases of anthrax, the modeling performed in this study found similar results as the literature (Wein et al 2003;Isukapalli et al 2008). Based on the survey results, some evidence exists that participants underestimated the risk downwind and overestimated how far it transfers perpendicular to the wind.…”
Section: Scenariossupporting
confidence: 83%
“…For outdoor releases of anthrax, the modeling performed in this study found similar results as the literature (Wein et al 2003;Isukapalli et al 2008). Based on the survey results, some evidence exists that participants underestimated the risk downwind and overestimated how far it transfers perpendicular to the wind.…”
Section: Scenariossupporting
confidence: 83%
“…Furthermore, without the full data set it is not possible to evaluate whether alternative dose-response models would have fit the data better than the log-probit model, which has been outperformed by other models in fitting other data sets [18]. Two studies [11], [15] applied a log-probit model based on the Jemski data to analyses of human exposure scenarios, although they applied ID 50  = 8,600 (the upper limit of the 95% confidence interval reported by Glassman).…”
Section: Resultsmentioning
confidence: 99%
“…ID estimates for age-dependent models rely on estimates of the age distribution of the United States population from the 2010 census. Criteria used to evaluate the models are 1) the parameter values are derived from dose-response data; 2) the shape of the dose-response curve is consistent with Sverdlovsk data; 3) the model is derived from mechanistic assumptions; and 4) the model estimates the incubation period.aPapers [11], [15] citing model J instead used ID 50  = 8,600, which is just within the 95% confidence limits reported in [26].bModels B2 and B3 estimate the time from exposure to infection take-off and death, but not the incubation period (time from exposure to onset of symptoms).cPapers [11], [15] citing model E1 instead used ID 50  = 8,600, which is within the range reported in the original paper.dFor model E5 , the original paper [32] estimated the time-dependent parameter θ from data and did not specify an estimate for r , but papers applying this model [11], [15] used the r value given above under an assumption of ID 50  = 8,600, comparable to other models based on expert opinion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Development of risk models is considerably complicated, as factors such as the size of the city population and its distribution, wind speed and direction, aerosol characteristics, temperature and humidity, population distribution within age groups, lung deposition pattern, and types of prophylaxes (e.g., vaccines, protective medical devices such as respirators) used are all factors that should be considered (Isukapalli et al 2008). This article focuses on one critical aspect of risk assessment: deposition of bioaerosols in the lungs.…”
Section: Introductionmentioning
confidence: 99%